(untitled) (Research, Society and Development, 2022)
This article aims to share and reflect on a case study involving the use of sustainable educational robotics in Youth and Adult Education (EJA). Interdisciplinary content was addressed, merging the teaching of robotics and sustainability through the use of materials that would be discarded. The study was applied in a multigrade EJA class in the countryside of Rio Grande do Sul. The methodological strategy adopted consisted of a bibliographic research, logbooks, and a qualitative approach. The students were immersed in an experience of awareness and development of competencies and skills related to sustainability and Industry 4.0. In this context, the proposal presented itself as viable and efficient, and compatible with the reality in which the students are inserted. It is worth emphasizing that the more this theme is disseminated, the more prepared the students will be for a future that will demand assertive solutions to socio-environmental problems. The process brought many learnings and findings, such as the sense of belonging, the urge to solve regional problems, and the fostering of critical thinking, which has the potential to extract and interpret the problems and, as a response, develop a viable, real, and low environmental impact solution. Among the results obtained we highlight autonomy, teamwork, problem solving, and self-management.